Views on “Good English” and “Nordic Exceptionalism” in Finland - Peterson, Elizabeth (Frontiers in Communication, 2022)
In the Nordic countries, widespread proficiency in English is positioned as a positive and even critical component of overall global competitiveness and competence. Indeed, maps illustrating who speaks the “best” English in Europe show a swath across the Nordic countries, and the number of people in the Nordic countries claiming proficiency in English is only a few percentage points below those in places such as the UK and Ireland. At the same time, the Nordic countries are routinely listed as the “happiest,” the most egalitarian, the most classless, least corrupt, and an epicenter for so-called “tender values.” In recent years, there has been a spate of publications highlighting how Nordic exceptionalism carries with it some unfortunate downsides, including the possibility for people to ignore or fail to acknowledge issues such as racism, sexism, and other social inequalities because of the affordance: “But our society is equal.” There is a parallel in the use of English. The entrenched notion that “everyone is good at English” overlooks that certain segments of the population—such as the elderly, immigrants and rural inhabitants—do not have the same level of access to the symbolic capital represented through facility in English. In this sense, the use of English presents social/class-based barriers that the national languages do not. This article offers a critique of the social realities relating to the use of English in the Nordic Countries within the context of the social welfare system and “Nordic exceptionalism,” focusing mostly on Finland. Making use of examples of discourse in newspapers, previous research and language policy documents, the chapter highlights how aspects of the use of English in Finland parallel other potentially hyped yet unequitable social issues.